2013
DOI: 10.1158/2326-6066.cir-13-0028
|View full text |Cite
|
Sign up to set email alerts
|

Immune Heterogeneity of Glioblastoma Subtypes: Extrapolation from the Cancer Genome Atlas

Abstract: Purpose The molecular heterogeneity of glioblastoma has been well recognized and has resulted in the generation of molecularly defined subtypes. These subtypes (classical, neural, mesenchymal, and proneural) are associated with particular signaling pathways and differential patient survival. Less understood is the correlation between these glioblastoma subtypes with immune system effector responses, immune suppression and tumor-associated and tumor-specific antigens. The role of the immune system is becoming i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
174
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(194 citation statements)
references
References 40 publications
18
174
0
2
Order By: Relevance
“…37 However, their occurrence in FL and DLBCL had not been reported previously, and their combination might differ from those evolved by other cancers. 38 Indeed, transcriptomes from biopsies do not identify which cells in these samples are expressing the immune checkpoint molecules. Therefore, our IHC study not only confirmed the expression of immune-evasion at the protein level, but also specified their respective distribution pattern, whether in tumor cells themselves or in their immune infiltrates.…”
Section: E1026530-8 Volume 4 Issue 8 Oncoimmunologymentioning
confidence: 99%
See 1 more Smart Citation
“…37 However, their occurrence in FL and DLBCL had not been reported previously, and their combination might differ from those evolved by other cancers. 38 Indeed, transcriptomes from biopsies do not identify which cells in these samples are expressing the immune checkpoint molecules. Therefore, our IHC study not only confirmed the expression of immune-evasion at the protein level, but also specified their respective distribution pattern, whether in tumor cells themselves or in their immune infiltrates.…”
Section: E1026530-8 Volume 4 Issue 8 Oncoimmunologymentioning
confidence: 99%
“…38 This list of genes was selected from a literature (Pubmed)-based search using the keywords: immunosuppressive cytokines, immunosuppressive mechanisms, chemokines, tumor-supportive myeloid genes, immunosuppressive myeloid and monocyte-related genes, immunosuppressive signaling pathway genes, synthesis of immunosuppressive metabolite, lymphocyte exhaustion marker, lymphocyte inhibitory receptor genes, Tregs genes, tumor immune escape, tumor immune evasion, tumor immune suppression. This search yielded the 54 relevant gene symbols which were selected for the IEGS ( Table 1).…”
Section: Ks Tests For Iegs Distribution Analysismentioning
confidence: 99%
“…These studies revealed distinct phenotypic states or subtypes that stratify gliomas and resemble different glial lineages (1)(2)(3). Although immunological gene expression classifications have been associated with clinical outcomes and prognosis (4,5), precision immunotherapy will ultimately rely on manipulation of the T-cell population that infiltrates gliomas and its underlying repertoire of T-cell receptors (TCRs). However, the structure and intertumoral heterogeneity of the TIL population in gliomas has not been described.…”
mentioning
confidence: 99%
“…The involvement of immune cells on glioma progression has been previously described [36][37][38]. Indeed, innate cell immunity and adaptive immune cell response have been implicated in glioblastoma progression [36,37,39,40].…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, innate cell immunity and adaptive immune cell response have been implicated in glioblastoma progression [36,37,39,40]. Interestingly, pathway analysis of the differentially methylated regions comparing initial versus recurrence has pinpointed an enrichment of immune response and mainly macrophage activation (i.e.…”
Section: Discussionmentioning
confidence: 99%